Effects of sizing on battery life and generation cost in PV–wind battery hybrid systems. (15th March 2022) - Bonkile, Mayur P.; Ramadesigan, Venkatasailanathan
Abstract: Battery energy storage system (BESS) is a crucial part of standalone renewable hybrid power systems. Dynamic battery degradation analysis and life prediction are essential for better techno-economic estimation of standalone PV–wind battery hybrid power systems. With this viewpoint, this paper aims to study battery degradation using a physics-based pseudo-two-dimensional (P2D) thermal battery model integrated with renewable PV–wind hybrid power systems and investigates the impact of BESS size variation on its degradation and its effect on the energy generation costs A power management and control strategy is developed to ensure continuous power flow with two regulation modes; (a) maximum power point tracking and (b) controlled power generation. Yearly real-world load data, operating, and ambient conditions are used to study five different percentage mixes of PV and wind power generation scenarios. For example, a mix of 70% PV-30% wind, 350 kWh BESS is needed (base case) based on the demand. The yearly degradation rate for this case is calculated to be 3.80%. The degradation rates vary from 3.80 to 2.33% per year for every 10% increment in the BESS size from the base case. Performing a techno-economic analysis reveals that the least energy generation cost is achieved when increasing the BESS size by 20%. This increases BESS life from 5.3 years to 7.3 years and reduces the generation cost from 35.19 ₹ kWh −1 (0.482 kWh −1 ) to 34.34 ₹ kWh −1 (0.470 kWh −1 ). These results provide essential insights to analyse the impact of BESS sizing on degradation and energy generation cost in a standalone PV–wind battery hybrid power system framework. The oversized BESS provides extended life and reduces the energy generation cost for a standalone PV–wind–battery hybrid power system. Graphical abstract: Highlights: PV–wind–battery hybrid power system framework for long term simulation. Physics-based P2D thermal battery model with SEI layer-based degradation. Power control strategy to track MPP or deviate from it to avoid dumping load system. Effect of BESS size variation on degradation and energy generation cost.